Attacks on passive optical networks from the subscriber end - N. N. Sergeev; V. N. Uryadov; S. S. Sheshporenok (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The analysis of construction principles of passive optical networks was carried out. Options for attacks on PON-network and attacks from the subscriber were discussed. The possibility of such attacks was evaluated. Method of protection from attacks by use of scheme of WDM-PON was proposed.